Hydrogen and electricity production with nuclear power plant and solar cells - SEÇKİN, CANDENİZ (My University, 2022)
oday’s world’s biggest problem is energy. The answer to this problem comes from hydrogen. Producing zero-emission fuel with zero-emission methods is what the world needs. The electricity produced by renewable sources mostly fluctuates to compensate that a nuclear power plant will generate constant electricity production. The advantages of a Nuclear Hybrid Energy System continues, due to the nuclear power plant’s safety regulations, there will be plenty of space to install Solar cells. In NHES the renewable power plants and nuclear power plants are competing with each other. The excess electricity or when the electricity demand is less than the hydrogen demand, the electricity will be converted to hydrogen via electrolysis. The most important part of this study is every component of the study is available and technologically ready..